2003
DOI: 10.1002/ppul.10379
|View full text |Cite
|
Sign up to set email alerts
|

Does vitamin D administered to children with asthma treated with inhaled glucocorticoids affect short‐term growth or bone turnover?

Abstract: Our objective was to assess whether administration of 25-OH-vitamin D to children with asthma treated with inhaled dry-powder budesonide 400 microg daily affects short-term growth or markers of bone turnover. We utilized a randomized, double-blind, two-period crossover trial with run-in and washout periods of 2 weeks and treatment periods of 4 weeks duration. The setting was an Outpatient clinic in a secondary referral center. Subjects included 14 boys and 3 girls with a mean age of 11.7 (range, 6.1-14.4) year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 43 publications
(60 reference statements)
0
43
0
Order By: Relevance
“…Although no studies to date have reported the effect of vitamin D supplementation during pregnancy and early infancy on asthma during childhood, placebo‐controlled clinical trials have shown efficacy of vitamin D supplementation in children with asthma. A meta‐analysis, published in 2015 , that included data from five clinical trials, which used a vitamin D doses ranging from 500 to 2000 IU/day in children aged 5–18 years, showed a statistically significant reduction in asthma exacerbations . One further trial published since this meta‐analysis, which enrolled 130 individuals aged 10–50 years and randomly assigned them to vitamin D or placebo, showed a significant improvement in lung function after 24 weeks of the intervention .…”
Section: Discussionmentioning
confidence: 99%
“…Although no studies to date have reported the effect of vitamin D supplementation during pregnancy and early infancy on asthma during childhood, placebo‐controlled clinical trials have shown efficacy of vitamin D supplementation in children with asthma. A meta‐analysis, published in 2015 , that included data from five clinical trials, which used a vitamin D doses ranging from 500 to 2000 IU/day in children aged 5–18 years, showed a statistically significant reduction in asthma exacerbations . One further trial published since this meta‐analysis, which enrolled 130 individuals aged 10–50 years and randomly assigned them to vitamin D or placebo, showed a significant improvement in lung function after 24 weeks of the intervention .…”
Section: Discussionmentioning
confidence: 99%
“…Asthma (Schou et al, 2003) COPD (Lehouck et al, 2012) Patients Children with asthma treated with inhaled dry-powder 182 patients with moderate to very severe COPD and a history of recent budesonide 400 mg daily exacerbations Interventions 15 mg (600 IU) 25-OH-vitamin D once daily in the 100,000 IU vitamin D supplementation or placebo every 4 weeks for morning with run-in and washout periods of 2 weeks 1 year and treatment periods of 4-week duration. Table 2.…”
Section: Typementioning
confidence: 99%
“…There were 2 randomized, placebo-controlled trials that showed the effects of vitamin D on asthma and COPD (Schou et al, 2003;Lehouck et al, 2012) (Table 2). The exacerbations did not significantly differ between the groups (including the median time to first exacerbation, exacerbation rates), nor did FEV1 and PEF (peak expiratory flow).…”
Section: Interventionmentioning
confidence: 99%
“…400 µg budesonide or beclomethasone from a dry powder inhaler), at which no other methods have been able to detect any systemic effects [5;62;67]. The method allows precise and direct comparisons of the systemic activity of different compounds [26;35;37;39], doses [27-29;35-37;40], dose intervals [30] and adjunctive [36] or modifying [51] treatments. Reduced lower leg growth has been attributed mainly to reduced linear bone growth [21].…”
Section: Resultsmentioning
confidence: 98%